Employer Consolidation and Wages: Evidence from Hospitals - Prager, Elena; Schmitt, Matt (American Economic Review, 2021)
We test whether wage growth slows following employer consolidation by examining hospital mergers. We find evidence of reduced wage growth in cases where both (i) the increase in concentration induced by the merger is large and (ii) workers’ skills are industry-specific. In all other cases, we fail to reject zero wage effects. We consider alternative explanations and find that the observed patterns are unlikely to be explained by merger-related changes besides labor market power. Wage growth slowdowns are attenuated in markets with strong labor unions, and wage growth does not decline after out-of-market mergers that leave local employer concentration unchanged. (JEL G34, I11, J22, J24, J31, J42, R32)